ANTIDIABETIC POTENTIAL OF SOLID LIPID NANOPARTICLES (SLNS) FROM KABAU SEED (ARCHIDENDRON BUBALINUM (JACK) I.C. NIELSEN) EXTRACT COATED WITH TRIMYRISTIN - Balqis, Solina; Diah Miftahul Aini; Muhammad Arif Fadilah; Nurkayah; Mu'awiyatu Al-Laitsi; Lia Aseptin Murdini; Elva Febriyanti (ALOTROP, 2025)
Type 2 diabetes mellitus is a global health problem that continues to increase. One alternative approach in managing diabetes is using natural materials with antihyperglycemic activity. This study aims to evaluate the effectiveness of solid lipid nanoparticles (SLN) containing Kabau seed extract (Archidendron bubalinum (Jack) I.C. Nielsen) coated with trimyristin in reducing blood glucose levels in hyperglycemic rats. Extraction was carried out by maceration using 96% ethanol, while SLN was synthesized by high-speed homogenization and ultrasonication methods. Particle size analysis showed an average diameter of 262.61 nm with a polydispersity index (PDI) of 0.144, indicating a homogeneous formulation. Phytochemical testing showed that Kabau seed extract contains alkaloids, flavonoids, tannins, and saponins contributing to antihyperglycemic activity. In vivo tests on Mus musculus showed that 20 % concentration of Kabau SLN reduced blood glucose levels by up to 97 mg/dL, approaching the effectiveness of metformin (104 mg/dL). Statistical analysis of ANOVA and BNT test showed significant differences between treatments. These results indicate that Kabau SLN has the potential as a candidate for phytopharmaceuticals in managing type 2 diabetes mellitus. Keywords: Diabetes mellitus; Kabau; solid lipid nanoparticles; trimyristin; flavonoids